2021
DOI: 10.1038/s41598-021-90969-y
|View full text |Cite
|
Sign up to set email alerts
|

Allele frequencies of single nucleotide polymorphisms of clinically important drug-metabolizing enzymes CYP2C9, CYP2C19, and CYP3A4 in a Thai population

Abstract: Prior knowledge of allele frequencies of cytochrome P450 polymorphisms in a population is crucial for the revision and optimization of existing medication choices and doses. In the current study, the frequency of the CYP2C9*2, CYP2C9*3, CYP2C19*2, CYP2C19*3, CYP2C19*6, CYP2C19*17, and CYP3A4 (rs4646437) alleles in a Thai population across different regions of Thailand was examined. Tests for polymorphisms of CYP2C9 and CYP3A4 were performed using TaqMan SNP genotyping assay and CYP2C19 was performed using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
(30 reference statements)
0
14
1
Order By: Relevance
“…These genes are highly polymorphic (e.g. CYP3A4/5 , CYP2B6 , CYP2C8 , CYP2C9 , CYP2C19 , CYP2D6 ) and are characterized by a wide geographic variability ( Zhou et al, 2017 ; Biswas et al, 2020 ; Sukprasong et al, 2021 ) interacting with large part of those drugs specifically used in COVID-19 ( Sukasem et al, 2013 ; Biswas et al, 2022 ). Interestingly, many clinical complications of COVID-19 belong to the same group of comorbidities responsible for the poor prognosis, and drugs acting as anti-inflammatory, antithrombotic (anti-coagulant and anti-aggregant), anti-hypertensive or with lipid-lowering action, have marked pharmacogenomics features resembling those belonging to the lipoproteins and homocysteine homeostasis genes ( Parmeggiani et al, 2008 ; Gemmati et al, 2009 ; Gemmati et al, 2016 ; Tisato et al, 2019 ; Cappadona et al, 2021 ; Tisato et al, 2021 ; Biswas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These genes are highly polymorphic (e.g. CYP3A4/5 , CYP2B6 , CYP2C8 , CYP2C9 , CYP2C19 , CYP2D6 ) and are characterized by a wide geographic variability ( Zhou et al, 2017 ; Biswas et al, 2020 ; Sukprasong et al, 2021 ) interacting with large part of those drugs specifically used in COVID-19 ( Sukasem et al, 2013 ; Biswas et al, 2022 ). Interestingly, many clinical complications of COVID-19 belong to the same group of comorbidities responsible for the poor prognosis, and drugs acting as anti-inflammatory, antithrombotic (anti-coagulant and anti-aggregant), anti-hypertensive or with lipid-lowering action, have marked pharmacogenomics features resembling those belonging to the lipoproteins and homocysteine homeostasis genes ( Parmeggiani et al, 2008 ; Gemmati et al, 2009 ; Gemmati et al, 2016 ; Tisato et al, 2019 ; Cappadona et al, 2021 ; Tisato et al, 2021 ; Biswas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that ~25% of the Thai population carried HLA-DQA1/ HLA-DQB1 genetic polymorphisms (Puangpetch et al, 2014; .5, and 1.8%, respectively. Approximately 30% of the CYP3A4 variant allele was identified in the Thai population as reported elsewhere (Sukprasong et al, 2021). Over 30% Thai population carried C3435T ABCB1 genetic polymorphisms as revealed in a previous study conducted in Thailand (Sensorn et al, 2013).…”
Section: Pharmacogenomics and Precision Medicine For Covid-19 In Thai...mentioning
confidence: 66%
“…The most prevalent and studied genetic variants of the CYP3A4/5, CYP2B6, CYP2C8, CYP2C9, CYP2C19, and CYP2D6 pharmacogenes have wide inter-ethnic variability. For example, CYP2D6*4 is highly prevalent in American population, whereas CYP2C19*2, *3 is highly prevalent in South Asians (Sukasem et al, 2013;Medhasi et al, 2016;Zhou et al, 2017;Biswas, 2021a;Sukprasong et al, 2021).…”
Section: Drug-metabolizing Enzymesmentioning
confidence: 99%
“…The performance evaluation showed notable results in this single system. The following estimated frequencies were obtained in our Thai-population-focused study: 3.7% in CYP2C9*2 and CYP2C19*3, 55.5% in CYP2C19*2, 77.7% in CYP2D6*10, and 14.8% in CYP2D6* 41. In previous studies, frequencies of only 0.08% for CYP2C9*2, 25.6% for CYP2C19*2 and 2.5% for CYP2C19*3 alleles were found in a Thai population (26,41). For CYP2D6 in Thai population, the decreased-function allele CYP2D6*10 is the most common allele found in patients treated with risperidone, at 51.8%, followed by CYP2D6*41 at 6.8% (42).…”
Section: Discussionmentioning
confidence: 86%